Introducing Istio service mesh for microservices : build and deploy resilient, fault-tolerant cloud-native applications - Posta, Christian; Sutter, Burr (O'Reilly Media, 2018)
Microservices fundamentally change the way you design enterprise software. By adding network dependencies to your application logic, you invite in a host of potential hazards that grow proportionally with the number of connections you make. With this practical ebook, DevOps teams will learn how to use the Istio service mesh to connect, manage, and secure microservices in order to create powerful cloud-native applications. Christian Posta and Burr Sutter from Red Hat introduce you to several key microservices capabilities that Istio provides on top of Kubernetes and OpenShift. You'll learn how your application can offload service discovery, load balancing, resilience, observability, and security to Istio so you can focus on differentiating business logic. You'll dive into Istio with detailed examples of: Traffic control: Examine Istio patterns including smarter canaries and dark launches Service resiliency: Discover how Istio provides load balancing, circuit breaking, and pool ejection Chaos testing: Test your system's ability to withstand turbulent conditions through fault injection Observability: Use tracing and metrics to learn the relationships between individual system components Security: Explore Istio's blacklist and whitelist security concepts.